Sensory Evaluation And β-Carotene Content Test in The Development of Yellow Pumpkin Brownies Products with The Substitution of Natural Sweeteners from Stevia Leaves (Stevia rabaudiana) - Julistin Haidiyanti; Arif Sabta Aji; Winda Irwanti; Faizah Rahma Putri; Raudah Nurjanah (Journal of Global Nutrition, 2025)
Excessive sugar consumption can lead to Type 2 Diabetes Mellitus (T2DM). Stevia is a low-calorie natural sweetener. Yellow pumpkin is abundant in antioxidants β-carotene. The utilization of stevia with yellow pumpkin as a functional food option can contribute to improved health benefits. To determine the effect of cane sugar with stevia substitution on sensory evaluation and β-Carotene concentration in steamed yellow pumpkin brownies. This was a quasi-experimental study approach utilizing a Completely Randomized Design (CRD). The experiment consisted of four treatments, each with different proportions of cane sugar and stevia. These treatments were labelled as P0 (100% cane sugar: 0% stevia), P1 (50% cane sugar: 50% stevia), P2 (25% cane sugar: 75% stevia), and P3 (0% cane sugar: 100% stevia). Hedonic tests are used to evaluate sensory features such as color, taste, aroma, and texture. Analysis of β-Carotene levels using the spectrophotometric method with a spectrophotometer. The data were subjected to analysis using One-way ANOVA. There was a significant influence on the sensory evaluation of taste, aroma, and texture (p<0,05). However, there was no significant impact on the color sensory assessment (p>0.05). The substitution of stevia leaf sweeteners had a significant effect on the concentration of β-carotene brownies (≤0,001), which was the highest concentration in P3 group (74.21 ± 0.74 μg/100 g). Replacing cane sugar with stevia has an important effect on the taste, aroma, texture, and levels of β-Carotene in brownies. Promising functional foods such as pumpkin and stevia have the potential of a healthy snack for T2DM patients.